Pengaruh Variasi Fraksi Volume Biokomposit Batang Padi Dan Resin Epoxy – Polyester Terhadap Kekuatan Tarik Dan Densitas - Naelendra, Ezza Ikhfan; Kencanawati, Cok Istri Putri Kusuma; Lokantara, I Putu (Teknik Desain Mekanika, 2024)
Abstract The purpose of this study was to determine the tensile strength and density of epoxy-polyester composites reinforced with rice stalks with volume fractions of 5%, 10%, 15%. This research uses rice straw as reinforcement and epoxy-polyester resin blend as filler. The stems used are 3cm in size. The molding process uses the Hand Lay-up technique with random fiber arrangement and uses ASTM D-3039, ASTM D 792-08 as a reference for tensile and density testing. The tensile test results obtained the highest tensile strength was in the 5% variation of 10.432 MPa. And the lowest tensile strength was in the 15% variation of 4.589 MPa. In the density test, the highest value was found in the 5% variation of 1.057 gr/cm3. And the smallest value in the 15% variation of 1.038 gr/cm3. This is reinforced from the observation of micro photos where the stem-reinforced composite at the 5% variation is able to bind perfectly with the matrix so that it has the highest tensile strength, but as the variation of rice stalks is added, the bonding that occurs is getting worse so that the pull out or detachment of the fibers from the matrix is increasing. It can be concluded that the composite with 5% variation of rice stalks has the maximum strength. Keywords : Rice straw stalk, Epoxy resin, Polyester resin, Volume fraction, Tensile test, Density test, micro photo